CLUSTERIZATION: EFFECTS ON SOME INDUSTRY SECTORS OF LITHUANIA - Kulikauskas, Darius; Viselgaitė, Daiva (Ekonomika, 2012)
In this paper we focus on clusterization in Lithuanian wood products manufacturing and in computer, electronic and optical products manufacturing industries. These sectors were chosen upon analyzing Jucevičius (2003) and Jucevičius (2009) who describe them as having undergone a clusterization process. We use graphical and statistical analysis to find that clusterization has had a positive effect on the mentioned industries. Our analysis also covers a brief review of clusterization theory, development and current state. We also note that clusterization is supported in the European Union, which might be one of the major reasons why it has been accepted in Lithuania. Finally, we argue that competent practitioners who focus on clusterization professionally are scarcely available in the labour market, and clusterization theory is far from mature and requires a lot of academic input.